9/9/90- in tribute to Bronislaw Zelek - Panayides, Angelos (My University, 2025)
Two years ago, Małgorzata's Bartosik book Bronisław Zelek. In the Letter Wonderland was published. It was created from the ground up – driven by a deep passion and fascination with his work, with the involvement of many people. This publication was made possible thanks to a successful Kickstarter campaign that was supported by nearly 300 people from several countries. This year, Zelek would have celebrated his 90th birthday. To mark this occasion, Małgorzata Bartosik organized an exhibition titled “9/9/90” – a presentation of nine original posters by Zelek, along with nine contemporary reinterpretations of these works, created by exceptional artists from around the world, as a celebration of his 90th birthday. This project will became a form of visual dialogue – a modern perspective on his work, which continues to inspire, even after all these years. It is a natural continuation of her book and another step in bringing this extraordinary figure back into the public eye. The exhibition was planned to be a satellite event of the 29th International Poster Biennale in Warsaw – a legendary design celebration that has shaped poster history for nearly 60 years. This year’s edition took place in early July.
9/9/90 – Nine Reinterpretations of Nine Posters by Bronisław Zelek on the 90th Anniversary of His Birth
Keywords: Poster, Exhibition